2021
DOI: 10.1002/cmtd.202100025
|View full text |Cite
|
Sign up to set email alerts
|

The Guerbet Reaction Network – a Ball‐in‐a‐Maze‐Game or: Why Ru‐MACHO‐BH is Poor in Coupling two Ethanol to n‐Butanol

Abstract: Invited for this month's cover is the group of Marcel A. Liauw at the RWTH Aachen University (Germany). The cover picture shows a playable version of the homogeneously catalyzed Guerbet‐coupling from ethanol to n‐butanol. The 2D ball‐in‐a‐maze‐game is shown here because the reaction steps are either performed in presence of a redox catalyst (top‐down) or in presence of a base (left‐right). Both axes can be moved independently from each other and substances are connected with humps in the height of the activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Likewise, consistent with Liauw's results 39 , with Ru-2 we found poor coupling of ethanol to 1-butanol. On the contrary, 830 ppm of Ru-2 catalyzed 2-butanol production with a yield of 8% and an 86% selectivity towards secondary alcohols (Entry 5).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Likewise, consistent with Liauw's results 39 , with Ru-2 we found poor coupling of ethanol to 1-butanol. On the contrary, 830 ppm of Ru-2 catalyzed 2-butanol production with a yield of 8% and an 86% selectivity towards secondary alcohols (Entry 5).…”
Section: Resultssupporting
confidence: 93%
“…These complexes are robust catalysts for a wide range of sustainable chemical transformations under mild reaction conditions [33][34][35][36][37][38] . However, in support of the ndings made by Wass 11 , Liauw recently suggested that consumption of ethoxide additive, via formation of NaOAc by ethyl acetate saponi cation, is a major reason for low yields of ethanol upgrading to 1butanol catalyzed by Ru-2 39 . Indeed, NaOEt is often used for Guerbet reactions promoting the aldol condensation of acetaldehyde and selective formation of 1-butanol and higher primary alcohols 10,11,13 .…”
Section: Resultsmentioning
confidence: 98%